Synthesis, Properties and Analytical Applications of Cerium(IV) Iodoselenite: A New Cation Exchange Material - Thomas, Rajeev (Asian Journal of Chemistry, 2010)
In order to combine the qualities of inorganic and a stable material with good chromatographic properties, a new inorganic cation exchanger cerium(IV) iodoselenite (CeISe) was synthesized. Sample-1 was chosen for detailed ion exchange studies due to its highest ion exchange capacity, good appearance and chemical stability. Characterization of the resin was done through determination of ion exchange capacity, distribution coefficients for various metal ions, chemical analysis, pH titration, FT-IR spectra and TG thermal analysis. The distribution coefficients (Kd) of 10 metal ions were determined in different electrolyte/electrolyte concentrations. The significance of the exchanger is revealed by the important separations. Based on the difference in distribution co-efficient (Kd) some analytically important binary separations of metal ions Ca2+/ Pb2+, Zn2+/Pb2+, Cd2+/Pb2+, Ni2+/Pb2+, Co2+/Pb2+ and Hg2+/Pb2+ and ternary separations Pb2+/Hg2+/Cd2+, Pb2+/Hg2+/ Zn2+ and Pb2+/Hg2+/Co2+ have been achieved. Practical utility of the material has been demonstrated by a heavy metal separation. It was found to possess high thermal stability and selectivity for lead, thus making it an important exchanger for the environmentalists.